Legal Protection of Personal Data of E-Commerce Users According to Indonesian Laws - Anik Kunantyorini (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2021)
In this rapidly developing era, the existence of the internet is not only for learning media, but can also be used as a promising source of income in today's era. In addition, the internet can also be used as a means of getting convenience in buying and selling transactions, because the ease of access to the internet today makes it very easy for people to make online transactions, besides being easy, this is considered more practical, especially during a pandemic that never ends like today. The rise of online shopping has resulted in new problems arising in the field of consumer protection law. One of the issues that need attention is the protection of personal data of consumers who carry out online shopping activities. The intended personal data such as family card numbers.